Heavy Metal Removal from Aqueous Solutions by Adsorption using Montmorillonite - GODE, FETHIYE (Asian Journal of Chemistry, 2010)
Removal of Cu(II), Zn(II), Cd(II) and Cr(III) from aqueous solutions by sorption on the clay from south west region of Anatolia was investigated. Experiments were carried out as a function of solution pH (2-8), initial solute concentration (1 × 10-4-1 × 10-3 mol/L), temperature (20-65°C), amount of adsorbent dosage (0.1-0.9 g) and time (5-2880 min) by batch process. Sorption characteristics of montmorillonite were evaluated by using Freundlich, Langmuir and Dubinin-Radushkevisch (D-R) adsorption isotherms. X-Ray diffraction, FTIR, SEM and elemental analysis were performed for characterization of clay. Concentrations of heavy metals in solution are determined by flame atomic absorption spectrometry.